ChemInform Abstract: New Septanoside and 20‐Hydroxyecdysone Septanoside Derivative from Atriplex portulacoides Roots with Preliminary Biological Activities. Issue 33 (August 2015) - Ben Nejma, Aymen; Nguir, Asma; Ben Jannet, Hichem; Hamza, M'hamed Ali; Daich, Adam; Othman, Mohamed; Lawson, Ata Martin
Abstract isolation, structure determination as well as antioxidant, antibacterial, and anticholinesterase activities of portulasoid (I) and septanoecdysone (II)